Association between guilds of birds in the African-Western Palaearctic region and the tick species Hyalomma rufipes, one of the main vectors of Crimean-Congo hemorrhagic fever virus - Tove Hoffman (Elsevier, 2021)
Introduction: The ecology of the vertebrate host contributes to the geographical range expansion of ticks. In this study, we investigated which tick taxa that infest and are dispersed by birds along African-Western Palaearctic flyways during northward migration, and whether bird ecology was associated with tick taxa. Materials and methods: Ticks were collected from birds trapped at bird observatories in Spain, Italy, Greece, and Israel during the spring migration of 2014 and 2015, using mist nets. The tick-infested bird species were classified into guilds, using different combinations of the variables: migration distance, wintering region, foraging behaviour, and winter habitat. Ticks were molecularly determined to genus and species level by sequencing fragments of the 12S ribosomal DNA (rDNA) gene and by phylogenetic inference, using the Maximum Likelihood algorithm. Data were analysed using descriptive measures, graphs, Chi2 tests, the Tukey-Kramer test, and a parametric linear model (generalized linear model) in order to analyse and adjust for characteristics in the bird guilds and their relationship to collected tick taxa. Results: Most (84.2%) of the 10,209 trapped birds were long-distance migrants, of which 2.4% were infested by ticks. The most common tick species was Hyalomma rufipes (77.7%; 447/575), a known vector and reservoir of Crimean-Congo hemorrhagic fever virus. Bird guilds containing only long-distance migrants with wintering areas in Africa were associated with the tick species H. rufipes (p < 0.0001). Furthermore, bird winter habitat was associated with H. rufipes (p = 0.003); with bird species overwintering in open habitat (p = 0.014) and wetlands (p = 0.046) having significantly more H. rufipes as compared to birds with a winter habitat comprising forest and shrubs (p = 0.82). Conclusions: With climate change, the likelihood of establishment of permanent Hyalomma populations in central and northern Europe is increasing. Thus, surveillance programs for monitoring the risk of introduction and establishment of H. rufipes in the Western-Palaearctic should be established. Our study suggests that migratory bird species wintering in African open habitats and wetlands are good candidates for monitoring potential introduction.